2016
DOI: 10.1016/j.ydbio.2016.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of UNC-130/FOXD-mediated mesodermal patterning in C. elegans

Abstract: Spatial polarity cues in animals are used repeatedly during development for many processes, including cell fate determination, cell migration, and axon guidance. In C. elegans, the body wall muscle extends the length of the animal in four distinct quadrants and generates an UNC-129/TGF-β-related signal that is much higher in the dorsal two muscle quadrants compared to their ventral counterparts. This pattern of unc-129 expression requires the activity of the proposed transcriptional repressor UNC-130/FOXD whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Unlike unc-130 , a well characterized and stably integrated unc-129p∷GFP transcriptional reporter Punc-129(4.2 Kb)∷gfp , which has 4.2 Kb sequences upstream of the translational start site of unc-129 driving the expression of GFP, shows robust expression in the dorsal embryonically-derived BWMs as previously reported (Kersey et al, 2016; Nash et al, 2000), but is not expressed in the M lineage (Figure 2H-N). Thus, unc-130, but not unc-129, is asymmetrically expressed in the ventral M lineage.…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…Unlike unc-130 , a well characterized and stably integrated unc-129p∷GFP transcriptional reporter Punc-129(4.2 Kb)∷gfp , which has 4.2 Kb sequences upstream of the translational start site of unc-129 driving the expression of GFP, shows robust expression in the dorsal embryonically-derived BWMs as previously reported (Kersey et al, 2016; Nash et al, 2000), but is not expressed in the M lineage (Figure 2H-N). Thus, unc-130, but not unc-129, is asymmetrically expressed in the ventral M lineage.…”
Section: Resultssupporting
confidence: 62%
“…Previous studies have shown that unc-130 is expressed in the ventral bodywall muscles (BWMs) to restrict the expression of UNC-129/TGFβ to the dorsal BWMs for proper neuronal axon migration (Colavita et al, 1998; Kersey et al, 2016; Nash et al, 2000). The postembryonic mesodermal M lineage also exhibits distinct dorsoventral asymmetry (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations